An experimental and theoretical study into the valence electronic structure of bicyclo[2.2.1]hepta-2,5-dione - Jones, Darryl; Bolorizadeh, M. A.; Brunger, M. J.; Saha, S.; Wang, F.; Gleiter, Rolf; Büber, Johannes; Winkler, D. A. (Journal of physics. B, Atomic, molecular and optical physics, 2006)
The results from an electron momentum spectroscopy (EMS) study of the outer valence electronic region of bicyclo[2.2.1]hepta-2,5-dione (C7H8O2) are reported for the first time. The measured binding energy spectra are presented for the azimuthal angles 0°, 10° and 0° + 10°, respectively, and are compared to new He(I) photoelectron spectroscopy results, which are measured as a part of this work. These experimental data are compared further with results from theoretical computations, using various methods including Hartree-Fock, density functional and an outer valence Green's function theory. Measured orbital momentum distributions are compared on an orbital by orbital basis against those obtained by calculations which employ the plane-wave impulse approximation. These calculations use orbital wavefunctions obtained from Hartree-Fock and density functional theory with a couple of generalized gradient approximation exchange correlation (XC) functionals and the DGauss triple zeta valence polarization basis set. Agreement between the measured and calculated momentum distributions was found to be only fair. Nonetheless, the orbital momentum distributions of the molecule still provide an orbital based assessment of the XC functionals of the density functional theory employed, and an understanding of the chemical bonding mechanisms within the species. Finally, the spectroscopic strengths calculated using outer valence Green's function theory are compared against those derived from our EMS measurements.
Gesehen am 30.10.2020